Nutrient limitation drives response of Calamagrostis epigejos to arbuscular mycorrhiza in primary succession - Rydlová, Jana; Püschel, David; Dostálová, Magdalena; Janoušková, Martina; Frouz, Jan (Mycorrhiza, 2016)
Little is known about the functioning of arbuscular mycorrhizal (AM) symbiosis over the course of primary succession, where soil, host plants, and AM fungal communities all undergo significant changes. Over the course of succession at the studied post-mining site, plant cover changes from an herbaceous community to the closed canopy of a deciduous forest. Calamagrostis epigejos (Poaceae) is a common denominator at all stages, and it dominates among AM host species. Its growth response to AM fungi was studied at four distinctive stages of natural succession: 12, 20, 30, and 50 years of age, each represented by three spatially separated sites. Soils obtained from all 12 studied sites were γ-sterilized and used in a greenhouse experiment in which C. epigejos plants were (1) inoculated with a respective community of native AM fungi, (2) inoculated with reference AM fungal isolates from laboratory collection, or (3) cultivated without AM fungi. AM fungi strongly boosted plant growth during the first two stages but not during the latter two, where the effect was neutral or even negative. While plant phosphorus (P) uptake was generally increased by AM fungi, no contribution of mycorrhizae to nitrogen (N) uptake was recorded. Based on N:P in plant biomass, we related the turn from a positive to a neutral/negative effect of AM fungi on plant growth, observed along the chronosequence, to a shift in relative P and N availability. No functional differences were found between native and reference inocula, yet root colonization by the native AM fungi decreased relative to the reference inoculum in the later succession stages, thereby indicating shifts in the composition of AM fungal communities reflected in different functional characteristics of their members.
Keywords: Spoil banks; Primary succession of plants; Soil Microbiology; Mycorrhizae; vývoj rostlin; mykorhiza; Plant Development; půdní mikrobiologie; Soil; lipnicovité; půda; Mycorrhizal growth response; Chronosequence; Time Factors; časové faktory; Poaceae